3D Dirac semimetal Cd3As2-based solid solutions growth and characterization - E. Arushanov; A. N. Nateprov; G. Cywinski; W. Knap (AIP Advances)
Recent advancements in II3V2 semiconducting compounds have garnered significant attention due to their unique electronic properties and potential applications. Materials like Cd3As2 and Cd3As2-based solid solutions, often referred to as three-dimensional analogs of graphene, exhibit intriguing phenomena such as high electron mobility and a Dirac semimetal band structure. This review summarizes recent research progress, covering a broad range of topics including crystal structure analysis, thin film fabrication, band structure studies, and various experimental findings such as classical transport behavior, Shubnikov-de Haas oscillations, magnetization, optical and magneto-optical effects, and electron spin resonance, all within the last three decades. By providing a comprehensive overview of these research areas, this review aims to highlight the current state of understanding and identify promising directions for future research in Cd3As2-based solid solutions.